Patch-clamp analysis of nicotinic synapses whose strength straddles the firing threshold of rat sympathetic neurons - Kullmann, Paul H. M.; Horn, John P. (Frontiers in Neuroscience, 2022)
Neurons in paravertebral sympathetic ganglia are innervated by converging nicotinic synapses of varying strength. Based upon intracellular recordings of excitatory postsynaptic potentials (EPSPs) with sharp microelectrodes these synapses were classified in the past as either primary (strong) or secondary (weak) by their ability to trigger postsynaptic action potentials. Here we present an analysis of 22 synapses whose strength straddled threshold, thereby distinguishing them from the original classification scheme for primary and secondary synapses. Recordings at 36° C were made from intact superior cervical ganglia isolated from 13 male and 3 female Sprague-Dawley rats and from 4 male spontaneously hypertensive rats. Ganglia were pretreated with collagenase to permit patch recording. By dissecting a 1 cm length of the presynaptic cervical sympathetic nerve as part of the preparation and through use of graded presynaptic stimulation it was possible to fractionate synaptic inputs by their distinct latencies and magnitudes, and by the presynaptic stimulus threshold for each component. Comparison of cell-attached extracellular recordings with intracellular recordings of synaptic potentials and synaptic currents indicated that straddling EPSPs are not an artifact of shunting damage caused by intracellular recording. The results also showed that in cells where a single presynaptic shock elicits multiple action potentials, the response is driven by multiple synapses and not by repetitive postsynaptic firing. The conductance of straddling synapses also provides a direct estimate of the threshold synaptic conductance (9.8 nS ± 7.6 nS, n=22, mean ± s.d.). The results are discussed in terms of their implications for ganglionic integration and an existing model of synaptic amplification.